VITAMIN D DEFICIENCY AND RISK OF OVERUSE MUSCULOSKELETAL INJURIES IN RECREATIONAL RUNNERS - Nel Geworkian; Paulina Malon; Aleksandra Trojańska; Anita Pieńkowska; Karol Śliwa; Natalia Hariasz; Martyna Pietz; Anita Szymańska (International Journal of Innovative Technologies in Social Science, 2026)
Recreational distance running provides substantial cardiovascular and metabolic benefits but is associated with a high burden of overuse musculoskeletal injuries, particularly bone stress injuries and medial tibial stress syndrome. Low vitamin D status is common in athletes, including endurance runners living at higher latitudes, and may adversely affect bone, muscle and tendon adaptation to repetitive loading.This narrative review synthesises current evidence on vitamin D metabolism, its roles in the musculoskeletal system and the relationship between serum 25-hydroxyvitamin D [25(OH)D] and overuse injuries in recreational and sub-elite runners. Electronic databases were searched for observational, interventional and review studies addressing vitamin D status, bone stress injuries, soft-tissue overuse conditions and determinants of 25(OH)D in endurance athletes, with particular emphasis on running cohorts and military populations exposed to similar mechanical loads.Observational and interventional data in military recruits and athletes show that low 25(OH)D status is consistently associated with a higher risk of bone stress injuries, whereas evidence for muscle strains, tendinopathies and non-specific musculoskeletal pain remains limited and heterogeneous. Studies in endurance athletes indicate that vitamin D insufficiency is frequent, especially during winter, at higher latitudes and in those training predominantly indoors or outside peak sunlight hours. However, few prospective studies have specifically examined recreational runners, and virtually no trials have tested whether correcting vitamin D insufficiency reduces overuse injury incidence beyond standard load management and nutritional strategies.Available evidence supports viewing vitamin D as one modifiable systemic factor within multifactorial overuse injury prevention in runners, rather than an isolated causal agent. Maintaining serum 25(OH)D at least above 50 nmol/L, and possibly around 75–100 nmol/L in runners at elevated risk of bone stress injuries, appears reasonable, particularly in those with limited sun exposure or features of relative energy deficiency. Well-designed prospective cohorts and randomized trials in recreational runners are needed to clarify causal effects and refine screening and supplementation recommendations.